Penyuluhan Kesehatan dan Pemeriksaan Kadar Gula Darah, Kolesterol Para Lansia di Wilayah Kerja UPT Kesmas Sukawati I. - nyoman mastra (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2020)
Penyuluhan Kesehatan dan Pemeriksaan Kadar Gula Darah, Kolesterol  Para Lansia di Wilayah Kerja UPT Kesmas Sukawati I. I Wayan Merta, S.KM., M.Si k, Nyoman Mastra, S.KM., S.Pd., M.Si1, Ida Ayu Made Sri Arjani, S.IP., M.Erg2 Mertaiwayan9@gmail.com AbstractDiabetes mellitus (DM) and cholesterol disease are health problems not only in developed countries but also in developing countries Indonesia, where the preparation is quite high. This disease can attack all age groups, even elderly people are very at risk of developing this disease because their organs are not functioning optimally. Based on data from the Public Health Unit Sukawati I, there are 25 people with Diabetes Mellitus in Kemenuh Village. Community service activities carried out in Banjar Tengkulak Mas Kemenuh Village with a target of 40 people. The method in community service activities is lecture and examination of Blood Sugar and Cholesterol.The results obtained for a high level of knowledge before counseling 5 people (10%), after counseling increased to 34 people (75%) For examination of blood sugar levels with normal categories as many as 32 people (69%), above normal are as many as 14 people (31 %). For parameters of cholesterol with normal categories as many as 27 people (67%) and categories above normal as many as 14 people (33%). For the elderly whose blood sugar and cholesterol levels are normal to be maintained by maintaining the lifestyle behavior that has been carried out. As for the elderly whose blood sugar and cholesterol levels are above normal, which is changing diet by reducing the amount of rice, and increasing consumption of vegetables and fruits, regular exercise, and getting enough rest and controlling health regularly to the doctor.